The meaning of the novel Ceroz and Batozar by Tere Liye (pierce's semiotic studies) - B. Syukroni Baso; Johar Amir; Kembong Daeng (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The objectives of this study are; (1) the meaning of the graund sign in the novel CerozBatozar by Tere Liye. (2) the meaning of the sign of the object in the novel CerozBatozar by Tere Liye. (3) the meaning of the interpretant sign in the novel CerozBatozar by Tere Liye. (4) implications for sastra learning in vocational schools. This type of research is qualitative research with a description method. The data of this study is in the form of words, sentences, in the novel Ceroz and Batozar which contain signs in the form of graunds, objects, interpretations. The source of the data in this study is the text of the novel Ceroz and Batozar by Tere Liye. Data collection techniques used through reading or reading technology, observation and recording, analysis techniques. The technique of validity, which is used trianggulation theory. The data analysis technique used in this study is an interactive model with three components of analysis, namely data reduction, data presentation, and drawing conclusions. The results showed that there are three signs of semiotics according to pierce in the novels of Ceroz and Batozar, namely graund, object, and interpretant.